Analysis of notch-loaded patch for dual-band operation - Shivnarayan; Vishvakarma B.R. (My University, 2025)
Analysis of notch loaded rectangular patch antenna for dual-band operation has been proposed, in which dual frequency behaviour is obtained by notch loading. The theoretical analysis is based on modal expansion cavity model. The resonance frequency changes with the variation in the length and width of the notch. Thus the input impedance, VSWR, return loss and bandwidth are calculated. The obtained resonance frequency ratio is variable from 1.17 to 1.77 with the length and width of the notch.